Pengaruh Struktur Modal, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Makanan dan Minuman Yang terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - clara florensita yulisa; Ickhsanto Wahyudi (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of capital structure, profitability and firm size on firm value. The population and sample in this study are the financial statements of 48 Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange in 2018-2021. This research technique uses classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test. The collection technique used the method of documentation and literature study. The results of the t-test (partial) can be seen that the first hypothesis which states that capital structure has a positive and significant effect on firm value is rejected. The second hypothesis which states that profitability has a significant positive effect on firm value is accepted. The third hypothesis which states that firm size has a significant positive effect on firm value is rejected. The magnitude of the coefficient of determination is 0.335 or equal to 33.5%. This value shows that the variables of Capital Structure, Profitability, and Company Size simultaneously affect the Company Value by 33,5%. While the rest (100% - 33.5% = 67.5%) is influenced by other variables outside this regression equation or variables not examined.